Multivalent Antimicrobial Peptides as Therapeutics: Design Principles and Structural Diversities - Liu, S. P. (Springer Netherlands, 2010)
This review highlights the design principles, progress and advantages attributed to the structural diversity associated with both natural and synthetic multivalent antimicrobial peptides (AMPs). Natural homo- or hetero-dimers of AMPs linked by intermolecular disulfide bonds existed in the animal kingdom, but the multivalency strategy has been adopted to create synthetic branched or polymeric AMPs that do not exist in nature. The multivalent strategy for the design of multivalent AMPs provides advantages to overcome the challenges faced in clinical applications of AMPs, such as: stability, efficiency, toxicity, maintenance of activity in high salt concentrations and under physiological conditions, and importantly overcoming bacterial resistance which is currently a leading health problem in the world. The multivalency strategy is valuable for moving multivalent AMPs toward clinical applications.